Compensation and Teachers' Turnover Intention in Indonesian State Islamic High School: Evidence from Banjarmasin - Dwicahyo, Mochammad Noor; Yuseran, Muhammad (Management of Education: Jurnal Manajemen Pendidikan Islam, 2025)
This research examines the influence of financial and non-financial compensation on turnover intention among teachers at State Islamic High Schools (SIHS) in Banjarmasin, addressing the lack of studies within Islamic education contexts. Using quantitative field research design, the study surveyed 136 teachers selected from a population of 206 through simple random sampling. Data was collected using a validated and reliable questionnaire, with analysis conducted through multiple regression. Results indicate that both financial and non-financial compensation have a significant negative effect on turnover intention. Financial compensation showed a t-value of –2.571 (p = 0.011), while non-financial compensation exhibited a stronger effect with a t-value of –7.075. The model's adjusted R² of 0.510 demonstrates moderate explanatory power, indicating that the two compensation variables can explain 51% of turnover intention variance. These findings underscore the importance of implementing equitable and competitive compensation systems, emphasizing monetary rewards and non-monetary benefits, to strengthen teacher retention and institutional stability in Islamic educational settings.